Effectiveness of Funding Forest Reclamation Measures for Ensuring Sustainable Development of Agricultural Regions in the South of the European Part of Russia - Korneeva, Evgeniya A. (Economy of Regions, 2020)
The environmental imperative of the strategy for the economic development of the Russian regions requires a shift from the dominant productive land-use model to a model that accepts and develops green technologies, including forest reclamation. The academic community has been discussing the low attractiveness of such an approach because of its low economic substantiation, based on the traditional practice of calculating additional crop production. The study aims to analyse whether funding the forest reclamation of arable land effectively stimulates their development in the Russian Federation and the creation of regional programmes for protective afforestation. The applied research methods include simulation, system analysis, compensation costs andmarketpricemethods. Aproposednewapproachemphasizesthepositiveimpactofforests, including sustainable development, environmental security of the agricultural sector, and the reduction of agricultural land degradation. The applicability of forest reclamation was confirmed for the forest-steppe and dry steppe zones of the Russian Plain. For slope arable land, the study substantiated the parameters of the area covered by forest, considering that water-regulating and protective forest plantations include the simplest hydraulic structures. The study identified regional costs for the implementation of necessary measures and described environmental and economic effects as the advantages of forest reclamation for agriculture. The dynamics of the main indicators of the effectiveness of anti-erosion measures depend on the zone, the steepness of the slope of arable land, the erosion hazard, and biotechnological features of forest plantations. The research results are important for ensuring sustainable development of agricultural Russian regions with a high risk of water erosion, withdrawal of eroded land from agriculture and reduction of cadastral value.